1970
DOI: 10.1111/j.1748-1716.1970.tb04791.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenesis of Peripheral Adrenergic Neurons in the Rat: Pre‐ and Postnatal Observations

Abstract: The early development of the peripheral adrenergic neurons of the rat was followed with the Falck‐Hillarp fluorescence technique. In the 13 day embryo small fluorescent sympathicoblasts with short processes were found in segmentally arranged groups along the dorsal aspect of the embryo. The larger sympathetic ganglia and the strongly fluorescent adrenal medullary cells were easily identifiable at this stage. In the 18 day embryo, fluorescent axon bundles were found in most larger nerve trunks. The outgrowing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
1

Year Published

1972
1972
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(71 citation statements)
references
References 28 publications
(19 reference statements)
7
63
1
Order By: Relevance
“…The decrease in the number of fibre bundles between d 14 and 21 supports the common assumption that ramification of fibres is at the expense of bundles of nerve fibres (Lundberg et al 1976 ;Cowen et al 1982 ;Hill et al 1983Hill et al , 1985Olson et al 1988). The ultrastructural data indicating that the fibre density at 14 d was approximately 70 % that at 21 d, is considerably different from the fluorescence histochemical data (Sandow & Hill, 1997 and unpublished observations) which showed that the fibre density at 14 d was approximately 30 % that at 21 d. The large discrepancy between the ultrastructural and fluorescence data supports the possibility that, in arterioles of younger animals, the catecholamine content may have been such that fibres were undetected with the fluorescence method (de Champlain et al 1970 ;Owman et al 1971). Fluorescence histochemical estimations of varicosity numbers were also at variance with ultrastructural data, which showed that varicosity numbers were not significantly different between the 2 ages.…”
Section: contrasting
confidence: 55%
“…The decrease in the number of fibre bundles between d 14 and 21 supports the common assumption that ramification of fibres is at the expense of bundles of nerve fibres (Lundberg et al 1976 ;Cowen et al 1982 ;Hill et al 1983Hill et al , 1985Olson et al 1988). The ultrastructural data indicating that the fibre density at 14 d was approximately 70 % that at 21 d, is considerably different from the fluorescence histochemical data (Sandow & Hill, 1997 and unpublished observations) which showed that the fibre density at 14 d was approximately 30 % that at 21 d. The large discrepancy between the ultrastructural and fluorescence data supports the possibility that, in arterioles of younger animals, the catecholamine content may have been such that fibres were undetected with the fluorescence method (de Champlain et al 1970 ;Owman et al 1971). Fluorescence histochemical estimations of varicosity numbers were also at variance with ultrastructural data, which showed that varicosity numbers were not significantly different between the 2 ages.…”
Section: contrasting
confidence: 55%
“…The constant total activity of AADC at this stage indicates that certain AADC-rich organelles completely develop earlier than the other AADC-lacking part of the organ. The total protein of heart was on the increase at this stage, while completion of network formation of sympathetic nerve terminals by the 12th day after birth and a prominent feature of mast cells in heart at early postnatal age have been reported (11). Therefore, it is hypothesized that the growth of AADC-lacking myocardium weakened the activity of AADC, presumably localized in peripheral sympathetic nerve terminals and or in mast cells.…”
Section: Discussionmentioning
confidence: 93%
“…Although it has been suggested that these changes were caused by prejunctional mechanisms (Mackenzie & Standen, 1980), we have observed in the right atria and in the ventricle that sensitivity to Iso decreased in parallel to the sensitivity to NA during development Tanaka et al, 1988a,b), and concluded that the changes were mainly postjunctional in nature. This decrease in sensitivity correlates well with the increase in sympathetic innervation in each region, as determined by examining responsiveness to tyramine Tanaka et al, 1988a,b), NA content (Iversen et al, 1967;Mirkin, 1972), intensity of the fluorescence of catecholamine containing fibres (De Champlain et al, 1970;Lipp & Rudolph, 1972), capacity for NA uptake and retention (Iversen et al, 1967) and by morphological observations (Gomez, 1958).…”
Section: Discussionmentioning
confidence: 99%